From Genotype to Phenotype: A Primer on the Functional Follow-Up of Genome-Wide Association Studies in Cardiovascular Disease. (February 2018) - Lin, Jennie; Musunuru, Kiran
Abstract : Genome-wide association studies have implicated many human genomic loci in the development of complex traits. The loci identified by these studies are potentially involved in novel pathways that contribute to disease pathophysiology. However, eventual therapeutic targeting of these pathways relies on bridging the gap between genetic association and function—a task that first requires validation of causal genetic variants, casual genes, and directionality of effect. Executing this task requires basic knowledge of interpreting genome-wide association study results and prioritizing candidates for further study, in addition to understanding the experimental methods available for evaluating candidate variants. Here, we review the basic genetic principles of genome-wide association studies, the computational and experimental tools used for identifying causal variants and genes, and salient illustrative examples of how cardiovascular loci have undergone functional investigation.